Circulating Troponin as measured by a sensitive assay for cardiovascular risk assessment in primary prevention - Leistner, David; März, Winfried (Clinical chemistry, 2012)
Measuring circulating cardiac troponin using novel sensitive assays has revealed that even minute elevations are associated with increased mortality in patients with coronary artery disease or even in the general population. Less well defined, however, is the incremental value of measuring circulating cardiac troponin I (cTnI) by a sensitive assay for risk assessment in primary prevention. METHODS: We measured circulating concentrations of cTnI, N-terminal pro-B-type natriuretic peptide (NT-proBNP), and high-sensitivity C-reactive protein (hsCRP) in 5388 individuals free of known cardiovascular disease recruited into the DETECT study, a prospective longitudinal population-based cohort study. We determined the prognostic implications for incident major adverse cardiovascular events (MACE) during 5 years of follow-up. RESULTS: Circulating cTnI was detectable in 19% of the subjects. Increased cTnI concentrations were associated with established risk factors for atherosclerosis and demonstrated a graded relationship with all-cause mortality and incident MACE during 5-year follow-up. A single measurement of cTnI significantly improved risk prediction over established risk factors, and also added prognostic information, when adjusted for serum concentrations of NT-proBNP and hsCRP. CONCLUSIONS: Minute increases in cTnI are associated with increased mortality and incident MACE in a large primary prevention cohort and, thus, identify contributors to cardiovascular risk not fully captured by traditional risk factor assessment.
Gesehen am 27.07.2018
Published online December 28, 2011